Acupuncture for insomnia after ischemic stroke: an assessor-participant blinded, randomized controlled trial. Issue 5 (October 2022) - Cao, Yan; Yan, Yin-Jie; Xu, Jian-Yang; Liwayiding, Abulikemu; Liu, Yi-Ping; Yin, Xuan; Lao, Li-Xing; Zhang, Zhang-Jin; Xu, Shi-Fen
Background: To date, there has been little focus on research into acupuncture for insomnia after ischemic stroke. Insomnia is one of the most common sequelae after ischemic stroke, and it is the most unrecognized modifiable risk factor. Objective: To evaluate the efficacy and safety of acupuncture for insomnia after ischemic stroke. Methods: In this assessor-participant blinded, randomized, controlled trial, 144 ischemic stroke patients with insomnia meeting Diagnostic and Statistical Manual of Mental Disorders (fifth edition, DSM -5) criteria were assigned to verum or sham acupuncture treatment (n = 72 per group) for three sessions per week over 4 weeks. The outcomes were the Insomnia Severity Index (ISI), Pittsburgh Sleep Quality Index (PSQI), stroke-specific quality of life (SSQoL), and Hospital Anxiety and Depression Scale (HADS) scores. Multiple objective sleep variables were recorded using actigraphy. Assessment was conducted at baseline, and thereafter once biweekly for the 4-week treatment and at 4 weeks of follow-up. Results: The verum acupuncture group had significantly greater improvements than the sham acupuncture group in sleep quality from 2 weeks into treatment throughout the follow-up, indicated by ISI scores and actigraphic variable SE (sleep efficiency). This greater improvement was also observed in the PSQI after 4 weeks of treatment throughout follow-up, as well as actigraphic variable TST (total sleep time), SSQoL and HADS scores at the end of treatment, and SSQoL and depression scores at follow-up. There was no significant difference between groups in the actigraphic variable SA (sleep awakenings). Adverse events were mild in severity, and their incidence was not significantly different between the two groups. Conclusion: Acupuncture appears to be efficacious, in terms of improving insomnia, related quality of life, and affective symptoms, for patients with ischemic stroke. Trial registration number: ChiCTR-IIC-16008382 (Chinese Clinical Trial Registry).